Medication Use and Costs Among Older Adults Aged 90 Years and Older in Italy - Zazzara, Maria Beatrice; Cangini, Agnese; Da Cas, Roberto; Ippoliti, Ilaria; Marengoni, Alessandra; Pierantozzi, Andrea; Poluzzi, Elisabetta; Zito, Simona; Onder, Graziano; the Italian Working Group on Medication Use in the Elderly, (Frontiers in Pharmacology, 2022)
Older adults are often affected by multiple chronic conditions and experience geriatric syndromes that may affect the risk/benefit profile of medications. Little is known on use of such medications in the older population. This study describes medication use and costs in Italian adults aged ≥ 90 years. Data from the 2019 Pharmaceutical Prescriptions database, concerning data on medications reimbursed by the Italian National Health Service, were analyzed in terms of prevalence and amount of use expressed as Defined Daily Dose/1000 users (DDD/1000 users/ day), accounting for different age groups and sex. All individuals aged ≥ 90 years used at least one medication, with a mean number of 3128 DDD/1000 users/day corresponding to an annual cost of 683 euros per user. Both use and costs linearly decreased with increasing age, with men accounting for a higher amount of DDD/1000 users and costs than women across all age groups. Antihypertensives (1330 DDD/1000 inhabitants), antiplatelet agents (337 DDD/1000 inhabitants), medications for peptic ulcer and gastroesophageal reflux (328 DDD/1000 inhabitants) and lipid-lowering agents (166 DDD/1000 inhabitants) were the most frequently used medications. We observed a progressive decrease in the usage of the majority of medications with increasing age, with the exception of antibiotics and antipsychotics. Individuals aged ≥ 90 years represent lower DDD/1000 users, with associated decrease in annual costs. Persistent use of preventive medications highlights potential lack of awareness regarding medication rationalization and guidance for optimizing prescriptions. Our findings highlight need for further initiatives to improve medications appropriateness in these older age groups.